Effects of Additives upon Percolation Temperature in AOT-Based Microemulsions - Mejuto, J. C.; Morales, J.; Moldes, O. A.; Cid, A. (Journal of Applied Solution Chemistry and Modeling, 2014)
In the present review the percolative phenomena has been analyzed. Percolation is related to transport phenomena in microemulsions, in particular the electric charge transport. The influence of different additives upon electric percolation has been commented. The effects of the additives considered upon the microemulsion properties appear to come about through their association with the surfactant interface. The effects of these agents on the ease with which interdroplet channels allowing transfer of droplet contents are formed are not only responsible for their effects on percolation temperature, but also have serious implications for the rates of fast chemical reactions performed in microemulsions.